Research Recommendations for Improving Measurement of Treatment Effectiveness in Depression - Kamenov, Kaloyan; Cabello, María; Nieto, Mónica; Bernard, Renaldo; Kohls, Elisabeth; Rummel-Kluge, Christine; Ayuso-Mateos, José L. (Frontiers in Psychology, 2017)
Background: Despite the steadily escalating psychological and economic burden of depression, there is a lack of evidence for the effectiveness of available interventions on functioning areas beyond symptomatology. Therefore, the main objective of this study was to give an insight into the current measurement of treatment effectiveness in depression and to provide recommendations for its improvement. Materials and Methods: The study was based on a multi-informant approach, comparing data from a systematic literature review, an expert survey with representatives from clinical practice (130), and qualitative interviews with patients (11) experiencing depression. Results: Current literature places emphasis on symptomatic outcomes and neglects other domains of functioning, whereas clinicians and depressed patients highlight the importance of both. Interpersonal relationships, recreation and daily activities, communication, social participation, work difficulties were identified as being crucial for recovery. Personal factors, neglected by the literature, such as self-efficacy were introduced by experts and patients. Furthermore, clinicians and patients identified a number of differences regarding the areas improved by psychotherapeutic or pharmacological interventions that were not addressed by the pertinent literature. Conclusion: Creation of a new cross-nationally applicable measure of psychosocial functioning, broader remission criteria, report of domain-specific information, and a personalized approach in treatment decision-making are the first crucial steps needed for the improvement of the measurement of treatment effectiveness in depression. A better measurement will facilitate the clinical decision making and answer the escalating burden of depression.